Closed-loop preparation method of self-lubricating composite material with copper embedded into graphite hole net

By adopting a closed-loop preparation method in the preparation of copper-based graphite composite materials, and using vacuum furnace equipment for sintering and copper liquid penetration, the mechanical strength and lubricating performance of existing materials under high temperature and heavy load conditions are solved, and higher material performance and lower production costs are achieved.

CN119710351AActive Publication Date: 2025-03-28CHENGDU RUNFENG ELECTRICAL CARBON CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510231000.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The existing preparation methods of copper-based graphite composite materials have problems such as low mechanical strength, high production cost, poor environmental protection and unstable lubricating performance, especially in high temperature and heavy load conditions.

Method used

A closed-loop preparation method is adopted, by mixing graphite powder, corn powder and lead powder in proportion, sintering and copper liquid penetration using vacuum furnace equipment to form a self-lubricating composite material with copper embedded in the graphite pore mesh.

Benefits of technology

The complete penetration of copper liquid and uniform distribution of pore mesh are achieved, the mechanical strength and lubricating performance of the material are improved, the production cost is reduced, and good stability is shown in high temperature and heavy load conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710351A_ABST
    Figure CN119710351A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of production of metal and graphite composite self-lubricating materials, in particular to a closed-loop preparation method of a self-lubricating composite material with copper embedded into a graphite hole net, which comprises the following steps: taking graphite powder, corn micro powder and lead powder as raw materials, fully and uniformly mixing all the raw materials according to a proportion, adding a forming agent, and uniformly stirring; placing the parison at the bottom of a crucible in vacuum furnace equipment, covering the parison with a graphite pore plate with holes, and placing a copper block capable of covering the volume of the parison after melting on the graphite pore plate; sintering the parison under vacuum according to a preset heating curve, decomposing and evaporating the corn micro-powder after being heated and expanded to form a through air hole structure, decomposing and carbonizing the forming agent, and connecting with the graphite powder to form the parison with through grids. According to the method, the mesh rate uniformity of the parison is remarkably improved, and higher permeation efficiency and composite strength are provided for subsequent molten copper infiltration; and holes in the parison are further dredged, and the permeability of the molten copper is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal and graphite composite self-lubricating material production, and in particular to a closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material. Background Art

[0002] Self-lubricating materials are an important basic material in the field of metallurgy and mechanical manufacturing. They are widely used in key components such as bearings, bushings, and guide rails because they can maintain good lubrication performance under high load, high temperature, and harsh environment of relative operation (movement). Among them, copper-based graphite composite materials have become a high-performance oil-free self-lubricating material that has attracted much attention because of their excellent thermal conductivity and electrical conductivity of copper and the self-lubricating property of graphite. However, in the existing technology, there are still many difficulties in how to prepare this high-quality material efficiently, at low cost, and in an environmentally friendly manner.

[0003] At present, the preparation methods of copper-based graphite composite materials mainly include three categories: the first is the traditional powder metallurgy method, which is to obtain a composite material by mixing copper powder and graphite powder, pressing and sintering; the second is the melt infiltration method (impregnation method), which is to force molten copper liquid to infiltrate the prefabricated graphite blank under non-vacuum conditions by applying pressure to form a composite material; the third is the embedded graphite method, which is to drill holes in the copper material through mechanical processing methods, and then embed the machined graphite cylinder into the copper material to form a mechanical composite material.

[0004] Although the powder metallurgy method has a simple process, it is limited by the fact that the calcination temperature of the pressed billet must be lower than the melting point of the copper alloy. The metal powder cannot be organically connected into a metal grid, which ultimately results in the mechanical strength of the prepared composite material being low and therefore unable to meet the requirements of heavy load and other working conditions.

[0005] The infiltration method is based on the excellent permeability and wettability of copper liquid. The pre-sintered blank is placed in a crucible and heated to above 1000°C, and then the molten copper liquid is poured into the crucible containing the blank, and the metal liquid is forced into the mesh of the graphite blank by pressurizing the metal liquid surface to fill the graphite blank. However, when the air in the graphite blank is compressed to the same pressure as the pressure applied to the liquid surface, the metal solution cannot pass through the isobaric gas layer, and the inside of the graphite blank cannot be filled with metal liquid. Therefore, the composite material produced will greatly reduce the overall performance of the material, and the high-temperature operation has a large labor load, a low safety factor, and great harm to the environment.

[0006] The production process of the inlay method is simple, but the machining is time-consuming, labor-intensive, and has high production costs. In addition, the thermal expansion coefficients of the two materials are different. When used in actual high-temperature conditions, the graphite column is easy to loosen. Therefore, the lubricating film cannot be effectively formed for a long time, resulting in lubrication loss. This method cannot form a three-dimensional lubricating surface.

[0007] In recent years, in order to improve the uniformity of graphite preform structure and the comprehensive performance of composite materials, some studies have attempted to modify graphite preforms by pretreating graphite powder or using additives. However, based on existing technologies, one is how to effectively achieve uniform distribution of pores during the preparation process while ensuring the filling degree and strength of the composite structure of copper liquid and graphite pores, which is still a technical difficulty that the industry urgently needs to break through. The second is how to achieve closed-loop preparation of graphite matrix pore formation and copper liquid pore filling, ensure interference caused by segmented processes, reduce production costs, and improve the comprehensive performance of materials. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material.

[0009] To achieve the above object, the technical solution adopted by the present invention is as follows: A closed-loop preparation method for a copper-embedded graphite mesh self-lubricating composite material comprises the following steps: S1: Graphite powder, corn powder and lead powder are used as raw materials, resin is used as a bonding agent, graphite powder is used as the main body of the self-lubricating material, corn powder is used as a pore-forming agent to form a multi-dimensional pore network penetrating the graphite matrix, and lead powder is used as a pore-clearing agent. All raw materials are fully mixed in proportion to form a graphite precursor to be formed into a pore network and stored for standby use; S2: Use a pressing device to press the precursor to prepare a blank shape that meets the requirements; S3: Take a vacuum furnace device, which includes an outer crucible and an inner crucible arranged in the outer crucible, put the preform into the bottom of the inner crucible of the vacuum furnace device, and set a plurality of leakage holes around and at the bottom of the inner crucible. Leave a certain distance between the bottom of the inner crucible and the outer crucible, take a graphite orifice plate to cover the preform, which plays a role in fixing the preform and guiding the flow of copper liquid, and place a copper block that can cover the volume of the preform after melting on the graphite orifice plate; S4: Turn on the vacuum furnace equipment, and sinter the preform according to the preset heating curve. When the sintering temperature reaches 200°C, the resin wrapping the graphite powder is solidified, and the preform is shaped. Turn on the vacuum and continue to heat up to 300-350°C. About 80% of the organic components of the corn powder decompose and evaporate after heating, burn and volatilize to form a penetrating pore structure, and the adhesive resin coating the graphite powder decomposes and carbonizes to connect the graphite powder with the graphite powder to form a preform with dense pores. When the temperature rises to above 375°C, the lead powder in the preform melts to dredge the free carbon powder particles formed by the corn powder remaining in the pores. Continue to heat until the copper block melts, and the copper liquid flows into the inner crucible of the preform through the graphite orifice plate and covers the preform with a pore network. Nitrogen or argon is introduced for pressurization to make the molten copper liquid completely penetrate the internal pore network of the preform to form a dense copper-embedded graphite pore network self-lubricating composite material; S5: The inner crucible is connected to an external lifting mechanism, which is started to lift the inner crucible to separate excess copper liquid and the composite solid preform. The liquid copper flows into the outer crucible through the leakage hole of the inner crucible, and the preform is pressurized and cooled. After cooling, the final product is taken out, completing the entire closed-loop preparation process from hole making to copper embedding at one time.

[0010] Furthermore, in the above step S1, the graphite powder is selected from one or both of natural graphite powder and artificial graphite powder and mixed in a certain proportion, the particle size of the graphite powder is between 30 mesh and 500 mesh, and the corn powder is peeled and ground to between 30 mesh and 200 mesh.

[0011] Furthermore, in the above step S1, the lead powder has a particle size ranging from 10 to 50 μm. The lead powder itself has a low melting point and a high specific gravity, and has good fluidity at high temperatures, but a large particle size will cause uneven mixing distribution and affect the dredging of the blank pores.

[0012] Furthermore, in the above step S1, the resin includes one of phenolic resin, epoxy resin or furan resin.

[0013] Furthermore, in the above step S2, the pressing equipment is a hydraulic press.

[0014] Furthermore, the prepared preform is placed at the bottom of the inner crucible of the vacuum furnace equipment, and the preform is covered with a graphite orifice plate to fix the preform and guide the flow of copper liquid. A pre-weighed copper block is placed on the graphite orifice plate, and then the inner crucible is placed inside the outer crucible, leaving a certain distance between the bottom of the inner crucible and the bottom of the outer crucible.

[0015] Furthermore, in the above step S3, the vacuum furnace equipment also includes a furnace body and a furnace cover, the furnace body is provided with a thermal insulation screen and a graphite heater, the inner crucible and the outer crucible are both located in the insulation layer, the inner crucible and the outer crucible overlap and contact, and a plurality of liquid leakage holes are provided on the inner walls on both sides and on the bottom of the inner crucible.

[0016] Furthermore, the lead powder in the blank becomes lead liquid after being heated and melted and flows downward, sinking to the gap reserved between the bottom of the inner crucible and the outer crucible. The flow of the lead liquid takes away the free carbon powder after the corn powder is coked, and then clears the pores between the graphite to facilitate the penetration of copper liquid. After the copper melts and covers the blank, protective gas is filled into the furnace body, and pressure is applied to make the molten copper liquid completely penetrate into the interior of the blank, forming a high-density copper-embedded graphite pore self-lubricating composite material.

[0017] Furthermore, a lifting mechanism is used to drive the inner crucible to rise, and the excess copper liquid flows to the outer crucible, and the copper liquid is separated from the blank. After cooling, the pressure is released and the protective gas is recovered.

[0018] Furthermore, in the above step S5, after the temperature in the vacuum furnace drops to below 200°C, the upper cover of the can body is opened and the preform is taken out to complete the preparation.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. According to the characteristic that the resin is completely cured when the temperature is raised to above 180°C, the graphite powder coated with the resin is connected due to the curing of the resin, so that the blank skeleton is formed; according to the characteristic that the residual carbon content of corn powder is low, the water and organic gas evaporated during the carbonization process will not react chemically with the raw materials to generate other substances and impurities; and the volume of corn powder will not shrink as the temperature rises, but will expand by about 20%, which can improve the pore-forming efficiency; as the temperature further rises, the corn powder begins to carbonize. When the temperature rises to above 350°C, the residual carbon powder is about 20%, and the volume also begins to shrink, becoming free corn carbon powder, which is beneficial to the blank formation. The melting point of lead powder is 375℃, and the state with better fluidity is above 450℃. The lead liquid takes away the free corn carbon powder and clears the pores during its downward flow. The lead liquid will not react with carbon and graphite under vacuum, and will flow downward into the space reserved between the inner and outer crucibles, which is convenient for recycling and reuse. The melting point of copper block is 1083℃, and the temperature for the best penetration of copper liquid is above 1150℃. After the copper block is melted to form copper liquid, it flows into the space formed by the inner crucible and the graphite orifice plate through the graphite orifice plate and covers the blank. Since the inside of the blank is completely in a vacuum state, the copper liquid can completely penetrate into the blank without resistance. 2. According to the design of the heating curve, the air is pressurized at about 1.5Mpa within 200℃, the heating rate is about 20℃ / hour, and the vacuum is turned on above 200℃ to try to eliminate the organic volatiles produced by resin solidification and corn flour carbonization; the temperature rises to 375℃, and the temperature is accelerated by 80℃ / h to 1200℃, the copper block is fully melted and flows into the inner crucible and covers the blank; 0.5-1Mpa nitrogen or argon is applied to the furnace to maintain pressure for 20-30 minutes, and then the lifting mechanism set on the furnace cover is opened to lift the inner crucible under the pressure state for solid-liquid separation; the furnace temperature drops to below 900℃ to release the pressure, and the furnace temperature drops to below 200℃ to open the furnace cover to take out the final product, which can realize a one-time closed loop to complete the entire preparation process; 3. The present invention cooperates with a special solid-liquid separation vacuum furnace device and a lifting mechanism for lifting the inner crucible. The inner crucible and the outer crucible overlap and contact each other. The outer crucible is used to collect lead liquid and excess copper liquid, so that the vacuum furnace is not polluted. The preform is placed in the inner crucible, and the lifting mechanism is used to lift the inner crucible to separate the inner crucible from the copper liquid. After the preparation is completed, there is no excess copper liquid on the surface of the preform, which saves the post-processing step and reduces the labor cost. 4. The self-lubricating composite material of copper embedded in graphite mesh prepared by the present invention has a wide range of applications. By adjusting the proportion of each component, the material can be used in different working conditions; the volume proportion of the graphite mesh is more than 60%, and the lubrication performance is good, which is suitable for oil-free high-temperature working conditions with higher speed and lower load; the volume proportion of the graphite mesh is less than 30%, and the mechanical strength is high, which is suitable for heavy-load high-temperature working conditions without lubricating oil at lower speed. Therefore, the self-lubricating composite material of copper embedded in graphite mesh prepared by the present invention has a wide range of usage conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a physical picture of Example 1; Figure 2 This is an electron microscope image of the material prepared by the ingredients of Example 1; Figure 3 This is a physical diagram of Example 2; Figure 4 This is an electron microscope image of the material prepared by the ingredients of Example 2; Figure 5 This is an electron microscope image of the material produced in the preparation method without adding lead powder; Figure 6 This is a physical picture of a self-lubricating composite material made of copper and graphite grids produced by the melt infiltration method (impregnation method); DETAILED DESCRIPTION

[0021] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0022] The invention discloses a closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material, comprising the following steps: 25-50wt% (mass percentage) of graphite powder, 10-25wt% of corn powder, 20-30wt% of resin and 10-30wt% of lead powder are used as raw materials for preparing graphite mesh, and a precursor of graphite mesh material is prepared and stored for later use.

[0023] The precursor is pressed by a hydraulic press to prepare a parison shape that meets the requirements. The parison is placed at the bottom of the inner crucible of the vacuum furnace equipment. There are many leakage holes around and at the bottom of the inner crucible, and the bottom of the inner crucible is kept at a certain distance from the outer crucible. The parison is covered with a graphite orifice plate to fix the parison and guide the flow of copper liquid. A copper block that can cover the volume of the parison after melting is placed on the graphite orifice plate.

[0024] The vacuum furnace equipment is turned on, and the preform is sintered under vacuum according to the preset heating curve, first completing the front-end process of graphite matrix pore making; as the temperature continues to rise, the copper block melts and flows into the surface of the preform through the graphite orifice plate, and nitrogen or argon is introduced for pressurization, so that the molten copper liquid completely penetrates the interior of the preform, completing the filling process of copper embedded in the graphite pore network. The inner crucible is raised to separate the residual liquid copper and solid materials, and the preform is pressurized and cooled to below 200°C, and the final product is taken out. It can be seen that the preparation process of material pore making and pore network filling is a closed loop. Furthermore, the closed loop is achieved through the vacuum furnace equipment and customized process conditions, and the entire preparation process is completed in one go.

[0025] It should be noted that the vacuum furnace equipment is derived from a solid-liquid separation device under vacuum state with application number CN202311725524.2. In this patent document, the structure and use method of the vacuum furnace equipment are specifically disclosed, and this application will not repeat them.

[0026] The amount of copper and graphite composite can be calculated based on the volume of the blank and the designed mesh ratio. Assuming the volume of the blank is , the pore size is The mass of the copper block is , then the calculation formula is , In actual production, after the preform is placed in the inner crucible, the space formed by the inner crucible and the orifice plate covering the preform must be larger than the volume of the preform. Assuming that the space is 1.5 times the volume of the preform, the mass of the copper block to be loaded when loading the furnace is , the calculation formula is: , where the density of copper is Pcu≈8.96g / cm³.

[0027] Example 1 This embodiment provides a closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material, which is composed of the following components in weight percentage: 50wt% graphite powder, 10wt% corn powder, 30wt% phenolic resin, and 10wt% lead powder, with a particle size range of 10-50μm. Assuming that the designed parison volume is 100cm 3 , the porosity of the blank is 40%, then the mass of the copper block loaded into the furnace is about 0.8Kg, and the actual amount of copper used in the blank is about 0.358Kg.

[0028] The preparation steps are as follows: graphite powder and corn powder are weighed in proportion, phenolic resin is added and mixed in a kneader, and then lead powder is added and mixed in a dry mixer to prepare a precursor material.

[0029] The precursor is pressed using a hydraulic press to produce a blank shape that meets the requirements.

[0030] Place the preform at the bottom of the inner crucible of the vacuum furnace equipment, cover the preform with a graphite plate with holes, and place a copper block on the graphite plate. Turn on the vacuum furnace equipment, sinter the preform according to the preset heating curve, as the temperature gradually rises, the copper block melts and flows into the surface of the preform through the graphite plate, and nitrogen or argon is introduced for pressurization, so that the molten copper liquid completely penetrates the interior of the preform.

[0031] After the pressurization is completed, the inner crucible is lifted to separate the preform and the liquid copper, and the temperature is gradually lowered to below 200°C to take out the final product. Figure 1 For the actual picture), (attached Figure 2 (Electron microscope image) The test results of various properties of the copper-embedded graphite mesh self-lubricating composite material of this embodiment are shown in Table 1.

[0032] Example 2 This embodiment provides a closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material, which is composed of the following components in weight percentage: 25wt% graphite powder, 25wt% corn powder, 20wt% phenolic resin, and 30wt% lead powder, with a particle size range of 10-50um. Assuming that the design parison volume is 100cm 3 , the porosity of the blank is 70%, the mass of the copper block loaded into the furnace is about 1.08Kg, and the actual copper consumption of the blank is about 0.627Kg The preparation steps are as follows: graphite powder and corn powder are weighed in proportion, phenolic resin is added and mixed in a kneader, and then lead powder is added and mixed in a dry mixer to prepare a precursor material.

[0033] The precursor is pressed using a hydraulic press to produce a blank shape that meets the requirements.

[0034] Place the preform at the bottom of the inner crucible of the vacuum furnace equipment, cover the preform with a graphite plate with holes, and place a copper block on the graphite plate. Turn on the vacuum furnace equipment, sinter the preform according to the preset heating curve, as the temperature gradually rises, the copper block melts and flows into the surface of the preform through the graphite plate, and nitrogen or argon is introduced for pressurization, so that the molten copper liquid completely penetrates the interior of the preform.

[0035] After the pressurization is completed, the inner crucible is lifted to separate the preform and the liquid copper, and the temperature is gradually lowered to below 200°C to take out the final product. Figure 3 For the actual picture), (attached Figure 4 (Electron microscope image) The test results of various properties of the copper-embedded graphite mesh self-lubricating composite material of this embodiment are shown in Table 1.

[0036] Comparative Example 1 (without adding lead powder) The comparative example provides a closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material, which is composed of the following components in weight percentage: 35 wt % of graphite powder, 35 wt % of corn powder, and 30 wt % of phenolic resin.

[0037] The preparation steps are as follows: graphite powder and corn powder are weighed in proportion to prepare a precursor material.

[0038] The precursor is pressed using a hydraulic press to produce a blank shape that meets the requirements.

[0039] Place the preform at the bottom of the inner crucible of the vacuum furnace equipment, cover the preform with a graphite plate with holes, and place a copper block on the graphite plate. Turn on the vacuum furnace equipment, sinter the preform according to the preset heating curve, as the temperature gradually rises, the copper block melts and flows into the surface of the preform through the graphite plate, and nitrogen or argon is introduced for pressurization, so that the molten copper liquid completely penetrates the interior of the preform.

[0040] After the pressurization is completed, the inner crucible is lifted to separate the preform and the liquid copper, and the temperature is gradually lowered to below 200°C to take out the final product. (See attached Figure 5 ) A copper-embedded graphite mesh self-lubricating composite material of this comparative example is shown in the accompanying drawings.

[0041] Comparative Example 2 The copper-embedded graphite mesh self-lubricating composite material is produced by the melt infiltration method (impregnation method), and is composed of the following components in weight percentage: 25 wt% graphite powder, 25 wt% corn powder, 20 wt% phenolic resin, 30 wt% lead powder, and 650 wt% copper block.

[0042] The preparation steps are as follows: graphite powder and corn powder are fully mixed in proportion, and finally resin is added and fully mixed to prepare a precursor of graphite grid material.

[0043] The precursor is pressed using a hydraulic press to produce a blank shape that meets the requirements.

[0044] Then sintered in a sintering furnace.

[0045] Put the sintered preform into a crucible and then heat it in an electric furnace. Put the copper into a medium frequency furnace to heat and melt it, and take it out after the preform is heated to about 1000℃. Pour the copper liquid melted to about 1200℃ into the crucible with the preform, and then put the crucible into a closed pressurized container, and introduce gas into the container to pressurize it to more than 5Mpa. Force the copper liquid to penetrate into the preform and maintain the pressure for about 10 minutes before releasing the pressure.

[0046] Open the container and pour out the excess copper liquid to separate the solid and liquid.

[0047] Take out the infiltrated blank and cover it with quartz sand to prevent excessive oxidation of the blank.

[0048] After the preform is cooled, it is taken out, the surface impurities are removed and the oxide layer is removed by mechanical processing to obtain the final product (see attached Figure 6 ).

[0049] The copper-embedded graphite mesh self-lubricating composite material of this comparative example is shown in the accompanying drawings.

[0050] Table 1, the ratio of materials used in Examples 1-2 of the present invention is different, and the proportion of copper mesh and graphite mesh is different. Comparison table of their mechanical strength.

[0051] surface

[0052] According to the above performance results, in Example 1 and Example 2, lead powder, as a material with high specific gravity and good fluidity, can take away free corn carbon powder in the pore network of the blank during the preparation process, thereby better unblocking the grid, helping to improve the uniform distribution of the pore network, and promoting the complete penetration of the copper liquid, thereby forming a dense grid structure with more complete penetration, and the prepared material can fully meet the design requirements.

[0053] In Comparative Example 1, the uniformity of the pore structure is low, and the presence of corn carbon powder in the composite material leads to poor integrity of the mesh formed by the penetration of copper liquid.

[0054] In Comparative Example 2, compared with Example 2, the melt infiltration method (impregnation method) is used for production. Since the preform is sintered first to form a graphite mesh, a large amount of air exists in the graphite mesh. Moreover, when the copper liquid is infiltrated, the pressurized mesh is in a non-vacuum state, and the copper liquid is forced to be pressed into the graphite preform mesh. The air in the graphite preform is compressed by the copper liquid. When the gas in the preform is compressed and the air pressure is the same as the pressure applied to the copper liquid surface, the permeability of the copper liquid is greatly reduced, and the formation rate of the copper grid is greatly reduced.

[0055] Figure 1 , Figure 3 This is a photo of the material prepared by the two ingredients in this preparation method. Figure 1 The volume of graphite grid accounts for about 60%, with good lubrication performance but low mechanical strength, which is suitable for high-temperature oil-free lubrication conditions with higher speed and lower load; Figure 3 Graphite grid accounts for about 30% of the volume, and its lubrication performance is not as good as Figure 1 , but the mechanical strength is relatively Figure 1 High, suitable for low speed, heavy load, high temperature and non-lubricating oil lubrication conditions.

[0056] Figure 2 , Figure 4 It is an electron microscope picture of the actual materials prepared by the above two ingredients in this preparation method. Figure 2The graphite grid accounts for a large proportion, and the copper grid accounts for a small proportion; Figure 4 The mesh accounts for a small proportion, and the copper mesh accounts for a large proportion.

[0057] Figure 5 This is an electron microscope image of the material produced without lead powder in this preparation method. The volume proportion of graphite in the ingredients is Figure 4 Similar, but with poorer copper grid formation.

[0058] Figure 6 This is a photo of a copper-embedded graphite mesh self-lubricating composite material produced by melt infiltration (impregnation). Figure 3 Completely consistent. However, the mesh formation in the center of the composite material is not perfect.

[0059] In summary, by adding corn powder to the preparation method of copper-based graphite composite materials, a coherent pore network can be formed in the blank during the sintering process. The addition of lead powder not only takes away the free carbon particles formed by the carbonization of corn powder, but also can significantly improve the uniformity of the pore rate of the material, which is more conducive to the flow of copper liquid to fill all the pores in the graphite blank, thereby improving the consistency of the overall quality of the composite material. At the same time, a reasonable selection of raw material ratios can obtain a copper-based-graphite composite material suitable for different working conditions. Only by using a vacuum furnace equipped with a solid-liquid separation device can the copper liquid infiltrate the blank without dead angles and solid-liquid separation at high temperature, and the blank will not be oxidized, and the closed-loop preparation of copper embedded in graphite pore network self-lubricating composite materials can be realized.

[0060] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.

Claims

1. A closed-loop preparation method for a copper-embedded graphite mesh self-lubricating composite material, characterized in that: The following steps are involved: S1: Graphite powder, corn powder and lead powder are used as raw materials, resin is used as a bonding agent, graphite powder is used as the main body of the self-lubricating material, corn powder is used as a pore-forming agent to form a multi-dimensional pore network penetrating the graphite matrix, and lead powder is used as a pore-clearing agent. All raw materials are fully mixed in proportion to form a graphite precursor to be formed into a pore network and stored for standby use; S2: Use a pressing device to press the precursor to prepare a blank shape that meets the requirements; S3: Take a vacuum furnace device, which includes an outer crucible and an inner crucible arranged in the outer crucible, put the preform into the bottom of the inner crucible of the vacuum furnace device, the inner crucible is provided with a plurality of leakage holes around and at the bottom, and a gap is left between the bottom of the inner crucible and the outer crucible, take a graphite orifice plate to cover the preform, which plays a role in fixing the preform and guiding the flow of copper liquid, and place a copper block that can cover the volume of the preform after melting on the graphite orifice plate; S4: Turn on the vacuum furnace equipment, and sinter the preform according to the preset heating curve. When the sintering temperature reaches 200°C, the resin wrapping the graphite powder is solidified, and the preform is shaped. Turn on the vacuum and continue to heat up to 300-350°C. The organic components of the corn powder are decomposed, evaporated and volatilized after being heated to form a penetrating pore structure. The adhesive resin coating the graphite powder is decomposed and carbonized to connect the graphite powder with the graphite powder to form a preform with dense pores. When the temperature rises to 375°C, the lead powder in the preform melts to dredge the free carbon powder particles formed by the corn powder remaining in the pores. Continue to heat until the copper block melts, and the copper liquid flows into the inner crucible containing the preform through the graphite orifice plate and covers the preform with a pore network. Nitrogen or argon is introduced to change the vacuum state to a positive pressure, so that the molten copper liquid completely penetrates the internal pore network of the preform to form a dense copper-embedded graphite pore network self-lubricating composite material; S5: The inner crucible is connected to an external lifting mechanism, which is started to lift the inner crucible to separate excess copper liquid and the composite solid preform. The liquid copper flows into the outer crucible through the leakage hole of the inner crucible, and the preform is pressurized and cooled. After cooling, the final product is taken out, completing the entire closed-loop preparation process from hole making to copper embedding at one time.

2. The closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material according to claim 1, characterized in that: In the above step S1, the graphite powder is selected from one or both of natural graphite powder and artificial graphite powder and mixed in a certain proportion, the particle size of the graphite powder is between 30 mesh and 500 mesh, and the corn powder is peeled and ground to between 30 mesh and 200 mesh.

3. The closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material according to claim 1, characterized in that: In the above step S1, the particle size of the lead powder ranges from 10 to 50 μm.

4. The closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material according to claim 1, characterized in that: In the above step S1, the resin includes one of phenolic resin, epoxy resin or furan resin.

5. The closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material according to claim 1, characterized in that: In the above step S2, the pressing equipment is a hydraulic press.

6. The closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material according to claim 5, characterized in that: The prepared blank is placed at the bottom of the inner crucible of the vacuum furnace equipment, and the blank is covered with a graphite orifice plate to fix the blank and guide the flow of copper liquid. A pre-weighed copper block is placed on the graphite orifice plate, and then the inner crucible is placed inside the outer crucible, leaving a gap between the bottom of the inner crucible and the bottom of the outer crucible.

7. The closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material according to claim 1, characterized in that: In the above step S3, the vacuum furnace equipment also includes a furnace body and a furnace cover, the furnace body is provided with a thermal insulation screen and a graphite heater, the inner crucible and the outer crucible are both located in the thermal insulation layer, the inner crucible and the outer crucible overlap and contact, and a plurality of liquid leakage holes are provided on the inner walls on both sides and on the bottom of the inner crucible.

8. The closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material according to claim 7, characterized in that: The lead powder in the blank is heated and melted to become lead liquid and flow downward, sinking to the gap reserved between the bottom of the inner crucible and the outer crucible. The flow of lead liquid takes away the free carbon powder after the corn powder is coked, and then clears the pores between the graphite to facilitate the penetration of copper liquid. After the copper melts and covers the blank, protective gas is filled into the furnace body and pressure is applied to make the molten copper liquid completely penetrate into the interior of the blank, forming a high-density copper-embedded graphite pore self-lubricating composite material.

9. The closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material according to claim 8, characterized in that: The inner crucible is driven up by a lifting mechanism, and the remaining copper liquid flows to the outer crucible, and the copper liquid is separated from the blank. After cooling, the pressure is released and the protective gas is recovered.

10. The closed-loop preparation method of a copper-embedded graphite mesh self-lubricating composite material according to claim 1, characterized in that: In the above step S5, after the temperature in the vacuum furnace drops to below 200°C, the upper cover of the can body is opened and the preform is taken out to complete the preparation.

Citation Information

Patent Citations

  • Solid-liquid separation device in vacuum state

    CN117398755A

  • Metal-matrix self-lubricating composite bearing material and preparation method thereof

    CN102168202A

  • Self-lubricating iron-base wear-resistant alloy

    CN1040627A

  • Preparation method of copper-based graphite self-lubricating material

    CN107419123A

  • Preparation method and application of crystalline flake graphite reinforced copper-based composite material

    CN110343896A